2013
DOI: 10.5755/j01.ms.19.2.4438
|View full text |Cite
|
Sign up to set email alerts
|

a-Hemihydrate Gypsum from Flue Gas Desulphurization Gypsum

Abstract: In this work, properties of sulphate technogenic raw material – flue gas desulphurization (FGD) gypsum have been investigated in order to obtain α-hemihydrate gypsum as gypsum binding material. FGD gypsum is produced as a by-product during the process of desulphurization of exhaust gas emitted in power stations heated by fuel containing sulphur. It has been determined that α-hemihydrate gypsum can be obtained from FGD gypsum under hydrothermal conditions at 125 °C and 130 °C. The compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The effects of metal ions such as Na + , K + , Mg 2+ , Cu 2+ , Al 3+ , and Fe 3+ on the crystal morphology and size of calcium sulfate whiskers in aqueous HCl solutions were also investigated. , The results revealed that Al 3+ ions resulted in bigger and shorter crystals of HH . Additives of succinic acid, sodium citrate, and maleic anhydride proved to be more effective morphology modifiers for crystals of α-HH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of metal ions such as Na + , K + , Mg 2+ , Cu 2+ , Al 3+ , and Fe 3+ on the crystal morphology and size of calcium sulfate whiskers in aqueous HCl solutions were also investigated. , The results revealed that Al 3+ ions resulted in bigger and shorter crystals of HH . Additives of succinic acid, sodium citrate, and maleic anhydride proved to be more effective morphology modifiers for crystals of α-HH.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The results revealed that Al 3+ ions resulted in bigger and shorter crystals of HH. 16 Additives of succinic acid, 17 sodium citrate, 18 and maleic anhydride 19 proved to be more effective morphology modifiers for crystals of α-HH.…”
Section: Introductionmentioning
confidence: 99%